Effects of addition of engineered ZnO nanoparticles on the stability of colloidal suspensions containing TiO2 interacting with sandy soil - Oliveira,Elizabeth Mendes de (2020)
Abstract The stability of colloidal suspensions of engineered nanoparticles in the environment is of great interest for the risk assessment and treatment of hazardous materials. The relevance of this study is due to the evidence that engineered nanoparticles have been produced and used in commercial products in large scale, especially ZnO and TiO2, which are transported through the environmental components interacting with soil and water, representing the high potential impact on the ecosystems. In this research, we newly investigated the influence of nanoparticles of zinc oxide (NPZnO) on the behavior of nanoparticles of titania (NPTiO2). The impact of parameters such as pH, zeta potential, ionic strength, electric conductivity, suspended nanoparticles size of the colloidal suspensions containing hazardous nanoparticles on its stability, were studied using experimental and theoretical approaches. Leaching experiments were carried out within a sandy soil column model. It was found that the NPTiO2 in suspensions enhance the stability of the nanoparticles colloidal suspensions, keeping higher nanoparticles concentrations, while NPZnO promotes rapid aggregation, improving the soil particle collector efficiency with a lower concentration in equilibrium in the colloidal suspension, which can be used for promoting environmental impact attenuation and mitigation.